Studi Preferensi Konsumen Terhadap Produk Sepatu Gunung - Wandhansari Sekar Jatiningrum; Hasan Mastrisiswadi (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2017)
Research on consumer preferences on mountain shoe products is crucial. Mountain shoes are an important tool in mountain climbing activities that are at risk. Errors in the design of a mountain shoe cause inconvenience to consumers. This article discusses the factors that affect consumer satisfaction of mountain shoe products, so get the appropriate product design. Data processing is done by Kano method that shows response from respondent tend to spread. Another finding is that the number of values between categories in some attributes has an insignificant difference. Determination of Kano category is done by using Kano's satisfaction coefficient graph. The results show that the dominating category is must-be, ie 9 attributes need to be a priority because it is a basic need that must be met.